2016
DOI: 10.1038/ncomms13337
|View full text |Cite
|
Sign up to set email alerts
|

DNA looping mediates nucleosome transfer

Abstract: Proper cell function requires preservation of the spatial organization of chromatin modifications. Maintenance of this epigenetic landscape necessitates the transfer of parental nucleosomes to newly replicated DNA, a process that is stringently regulated and intrinsically linked to replication fork dynamics. This creates a formidable setting from which to isolate the central mechanism of transfer. Here we utilized a minimal experimental system to track the fate of a single nucleosome following its displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 69 publications
3
24
0
Order By: Relevance
“…Transfer of the nucleosome core from one DNA substrate to another, as illustrated in Figure 5 , is another characteristic of CENP-A nucleosomes that has not been directly visualized before. Evidence of interstrand nucleosome transfer was presented and discussed in landmark studies ( 32 , 33 ) and was recently demonstrated in a magnetic tweezers study ( 34 ). Furthermore, our results directly support such an ability.…”
Section: Discussionmentioning
confidence: 95%
“…Transfer of the nucleosome core from one DNA substrate to another, as illustrated in Figure 5 , is another characteristic of CENP-A nucleosomes that has not been directly visualized before. Evidence of interstrand nucleosome transfer was presented and discussed in landmark studies ( 32 , 33 ) and was recently demonstrated in a magnetic tweezers study ( 34 ). Furthermore, our results directly support such an ability.…”
Section: Discussionmentioning
confidence: 95%
“…2c) (43). In line with these observations, studies using optical tweezers have demonstrated that T7 helicase can displace DNA-bound proteins, such as a nucleosome or RNA polymerase (RNAP), under the assistance of an external force, indicating that helicase might clear away roadblocks during replication (25,44,45). In some cases, the replisome may rely on obstacles to terminate replication.…”
Section: Replicative Helicases Unwind Through Obstaclesmentioning
confidence: 77%
“…Unzipping DNA reveals a detailed and distinct force signature shaped by the underlying energy landscape of its sequence, and thus unzipping also serves as a powerful tool for probing and localizing protein-DNA interactions 5,[25][26][27] . A bound protein presents a roadblock which increases resistance to unzipping, resulting in a detectable rise in force above the naked DNA baseline when the unzipping fork encounters the protein.…”
Section: Fork Breathing Fluctuations Modulate Protein Unzippingmentioning
confidence: 99%
“…The generation of stretching and unzipping templates has been described previously 25,39,40 . For forming DNA dumbbell tethers, carboxylated beads (Polysciences) were coated with (either) streptavidin and anti-digoxigenin in house.…”
Section: Stretching and Unzipping Experimentsmentioning
confidence: 99%